2021
DOI: 10.3389/feduc.2021.588472
|View full text |Cite
|
Sign up to set email alerts
|

Motivational and Emotional Orientation, Engagement, and Achievement in Mathematics. A Case Study With One Sixth-Grade Classroom Working With an Electronic Textbook on Fractions

Abstract: Interactive and adaptive scaffolds implemented in electronic mathematics textbooks bear high potential for supporting students individually in learning mathematics. In this paper, we argue that emotional and behavioral engagement may account for the effectiveness of such digital curriculum resources. Following the general model for determinants and course of motivated action, we investigated the relationship between students’ domain-specific motivational and emotional orientations (person)—while working with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 112 publications
0
3
0
Order By: Relevance
“…In this case, it can be said that students have positive experiences in courses and gain learning motivation; the teachers can increase the sense of autonomy and satisfy the need for autonomy by shifting the responsibility to students and enabling them to make decisions themselves. Also, Reinhold et al's (2021) data showed that students with higher anxiety were less motivated. Additionally, Kuhfeld et.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, it can be said that students have positive experiences in courses and gain learning motivation; the teachers can increase the sense of autonomy and satisfy the need for autonomy by shifting the responsibility to students and enabling them to make decisions themselves. Also, Reinhold et al's (2021) data showed that students with higher anxiety were less motivated. Additionally, Kuhfeld et.…”
Section: Discussionmentioning
confidence: 99%
“…The studies in this review conceptualized engagement in many different ways (see Appendix C 4 and D 6 ), with most (n = 6) approaching engagement through two dimensions (e.g., cognitive and emotional [69]) or by only one dimension (n = 4, e.g., cognitive [70]). One study [71] referred to all four dimensions, three studies conceptualized engagement through the three dimensions of behavioral, affective/emotional and cognitive [77,81,90], and one study [87] included the three dimensions as well as SRL. Whilst such conceptualizations were detailed and well-referenced, there were some studies that only referred to engagement after the introduction and background (e.g., [72,73]), leaving it up to the reader to infer how engagement was understood, or that cited a few articles that had explored engagement within their introduction but did not then provide any insight into the conceptualization that was used in in their studies (e.g., [74]).…”
Section: How Does Engagement Theory Inform Data Analysis In K-12 La R...mentioning
confidence: 99%
“…In four studies, researchers employed modelling techniques to understand and predict student behaviors, including a prediction model for college attendance [80], an early warning model, based on deep learning and machine learning mechanisms [15], a model that distinguishes a learner's guessing behavior from solution behavior [83], and an unsupervised deep learning model to model students' SRL patterns [68]. Finally, prediction methods were used in two studies [15,90].…”
Section: Data Sourcesmentioning
confidence: 99%
“…Behavioral engagement is the individual's willingness, intensity, and concentration to achieve a target and stay focused on the final goal [59,60]. This attitude also signifies perseverance and determination when facing difficulties.…”
Section: Theory Of Engagementmentioning
confidence: 99%
“…Affective engagement is about individuals' emotions concerning what they are doing [63]. Another source explained this phenomenon as the quality of emotional reactions while performing an activity, as indicated by an individual's enthusiasm, enjoyment, pleasure, and satisfaction [60,64]. In this context, this engagement refers to the feelings related to the teaching process.…”
Section: Theory Of Engagementmentioning
confidence: 99%